The determinant factors of successful franchise business in Malaysia - Mohd Harif, Mohd Amy Azhar; Chee, Hee Hoe; Hussin, Zolkafli; Md Isa, Filzah; Othman, Siti Norezam (World Business Institute, Australia, 2011)
This paper presents the findings of a study in identifying the critical success factors of Bumiputra and non-Bumiputra franchisors in conducting their franchise business in Malaysia.The cross case study approach was used to analyse the data.Thirteen franchisors (six Bumiputra and seven non-Bumiputra) were selected as the sample cases.There were two important variables which had been identified as very critical to the success of local franchise business namely, marketing orientation factors and entrepreneurial based factors.The Bumiputra franchisors highlighted competition as their main business market orientation factor, while non-Bumiputra franchisors scored high for customer orientation in the product dominant sector.Franchisors from both ethnic groups demonstrated high entrepreneurial based factors.For the service dominant sector, the non Bumiputra franchisors emphasized on customer and competition orientation, whereas, the Bumiputra franchisors stressed more on customer and interfunctional coordination.However, the Bumiputra franchisors scored moderate achievement motivation and low risk taking as well as innovation.The non Bumiputra franchisors scored high in the entrepreneurial based factors.